Characterization and properties of blended bottom ash fly ash for geopolymer brick - Laila Mardhiah Deraman (School of Materials Engineering, 2019)
The aim of this research is to focus on the development of bricks using blended bottom ash and fly ash as raw material by using the geopolymerization process. The objectives of this research are listed; to characterize bottom ash as new source material for geopolymerization; to obtain the best percentage of fly ash for geopolymer bricks based on compressive strength; to determine the optimum of sodium silicate (Na2SiO3) to sodium hydroxide (NaOH) ratio and solid to liquid ratio of the blended bottom ash and fly ash geopolymer brick based on compressive strength; to investigate thermal conductivity, thermal diffusivity and specific heat of the blended bottom ash and fly ash geopolymer bricks.